The Potential of Anti-Diabetic Rākau Rongoā (Māori Herbal Medicine) to Treat Type 2 Diabetes Mellitus (T2DM) Mate Huka: A Review - Koia, Jonni Hazeline; Shepherd, Peter (Frontiers in Pharmacology, 2020)
T2DM (or Māori term ‘mate huka’) is a major long-term health issue in New Zealand particularly among the Māori community. Non-insulin drugs commonly used in New Zealand for the treatment of T2DM have limits to their efficacy as well as side effects, which are of concern for diabetics. As such, the potential for natural products such as traditional rākau rongoā are of interest for potentially preventing the development of T2DM or improving the treatment of the disease. In particular, anti-diabetic effects have been reported for rākau rongoā such as karamu, kūmarahou and kawakawa. Natural products have been identified in karamu, kūmarahou and kawakawa that have documented potential effects on glucose metabolism that could contribute to the anti-diabetic effect of these rākau rongoā. As such, this could provide scientific insight into the mātauranga (traditional knowledge) developed over generations by Māori. However, detailed laboratory based and clinical studies would be required to understand and validate these properties of karamu, kūmarahou and kawakawa, and to understand how they can be used in T2DM treatment. Social determinants of indigenous health such as language, culture, traditional knowledge and identity, are important in understanding the relationship Māori have with their land and the mātauranga they developed of the medicinal properties within their rākau rongoā, over many centuries. Interestingly, traditional Māori views towards scientific research using animal models to test rākau rongoā are varied but supportive. Furthermore, cultural issues surrounding Māori mana motuhake (self-determination) of traditional rongoā Māori healing practices and the inequity faced by many kairongoā (rongoā Māori practitioners) and tohunga (healers) compared to mainstream health are a current issue within the New Zealand health system. As such, a cultural holistic approach for T2DM care among Māori would be advantageous. This review will outline the available evidence supporting the anti-diabetic efficacy of karamu, kūmarahou and kawakawa. Currently though there is a lack of molecular research to understand the mechanisms of this efficacy, as such this review will also outline Te Reo Tipu Research, a kaupapa Māori framework for molecular and genomic research on taonga flora.